Extracellular Vesicles From LPS-Treated Macrophages Aggravate Smooth Muscle Cell Calcification by Propagating Inflammation and Oxidative Stress - Yaker, Linda; Tebani, Abdellah; Lesueur, Céline; Dias, Chloé; Jung, Vincent; Bekri, Soumeya; Guerrera, Ida Chiara; Kamel, Saïd; Ausseil, Jérôme; Boullier, Agnès (Frontiers in Cell and Developmental Biology, 2022)
Background – Vascular calcification (VC) is a cardiovascular complication associated with a high mortality rate among patients with diseases such as atherosclerosis and chronic kidney disease. During VC, vascular smooth muscle cells (VSMCs) undergo an osteogenic switch and secrete a heterogeneous population of extracellular vesicles (EVs). Recent studies have shown involvement of EVs in the inflammation and oxidative stress observed in VC. We aimed to decipher the role and mechanism of action of macrophage-derived EVs in the propagation of inflammation and oxidative stress on VSMCs during VC. Methods – The macrophage murine cell line RAW 264.7 treated with lipopolysaccharide (LPS-EK) was used as a cellular model for inflammatory and oxidative stress. EVs secreted by these macrophages were collected by ultracentrifugation and characterized by transmission electron microscopy, cryo-electron microscopy, nanoparticle tracking analysis, and the analysis of acetylcholinesterase activity, as well as that of CD9 and CD81 protein expression by western blotting. These EVs were added to a murine VSMC cell line (MOVAS-1) under calcifying conditions (4 mM Pi – 7 or 14 days) and calcification assessed by the o-cresolphthalein calcium assay. EV protein content was analyzed in a proteomic study and EV cytokine content assessed using an MSD multiplex immunoassay. Results – LPS-EK significantly decreased macrophage EV biogenesis. A 24-h treatment of VSMCs with these EVs induced both inflammatory and oxidative responses. LPS-EK-treated macrophage-derived EVs were enriched for pro-inflammatory cytokines and CAD, PAI-1, and Saa3 proteins, three molecules involved in inflammation, oxidative stress, and VC. Under calcifying conditions, these EVs significantly increase the calcification of VSMCs by increasing osteogenic markers and decreasing contractile marker expression. Conclusions – Our results show that EVs derived from LPS-EK–treated-macrophages are able to induce pro-inflammatory and pro-oxidative responses in surrounding cells, such as VSMCs, thus aggravating the VC process.